Function and Hierarchy of Settlement in Regional Development Corridor Malaysia: A Case Study of South-East Pahang Development Authority (DARA) - BIN MASAMUDDIN, AMIRUL ASYRAF; Rashid, Mohamad Fadhli (Department of Urban and Regional Planning, Universitas Diponegoro, 2022)
Frontier area development through rural development is one of strategy in the regional development corridors (RDC) that was formulated by the government. In line with the New Economic Policy (NEP) strategy, the development of RDC such as South-East Pahang Development Authority (DARA) in 1971 was focused on improving the living standards and productivity of the rural population through the process of modernizing rural and remote areas. The existence of DARA indirectly catalysed the development of new townships which drove the urbanization process in the South-East Pahang region. However, the dissolution of DARA in 2000 was occurred due to the successful in the development of DARA in South-East Pahang region. Nonetheless, a question emerges whether these new townships are fulfilling to the settlement’s function and hierarchy performances today that was planned in early setup of DARA. Hence, this paper aims to evaluate the settlement’s function of the township development in the DARA in Malaysia as a case study of RDC based on the level of readiness public and basic facilities in a settlement area with using 4 settlement services indicator such as function, economy, public / social facilities and convenience infrastructure and utility. The methodology used is a qualitative method using a case study method on the 11-existing settlement centers located in the DARA area. The findings highlighted that the settlement’s function of these settlement centers have undergone significant changes from the main goal of its establishment with today’s functions and performances due to the factor of population decline and shrinkage of economic opportunity. Therefore, immediate measures are required by the relevance government agencies to ensure the existence of these settlement centers in the future as well as to ensure that the settlement area meets the needs of the population equipped with adequate facilities for socio-economic activities.